Studi Penggunaan Agregat Sungai Bittuang Sebagai Bahan Campuran AC-WC - Nilamsari Wendani; Mary Selintung; Alpius (Paulus Civil Engineering Journal, 2020)
The purpose of this study was to determine the aggregate characteristics of the Bittuang River, determine composition of the AC-WC mixture and find out the Marshall characteristics, the remaining Immersion Index in the AC-WC mixture. The methodology in this research was to conduct a series of characteristics testing in the form of coarse aggregates, fine aggregates, fillers,and asphalt and then design a mixture composition then make test specimens in the form of AC-WC and Marshall Conventional testing. The results showed that the aggregate characteristics originating from the Bittuang River, Tana Toraja Regency, for the AC-WC mixture met the spesifications required by the 2018 Bina Marga standards. Based on the design of the composition of the mixture of AC-WC using Bittuang River aggregate is 36.90% coarse aggregate, 50.30% fine aggregate, 5.80% filler, with optimum asphalt content of 7.00%. The results of testing the characteristics of the AC-WC mixture through conventional Marshall tests obtained the characteristics of a mixture derived from meeting the specifications of stability, flow, VIM, and VFB, while for VMA it does not meet the specification requirements 5.00% asphalt content. While the Marshall Immersion test results (Residual Strength Index) on the mixtureof Laston AC-WC using aggregate Bittuang River, Bittuang District Tana Toraja Regency met the General Spesifications of the 2018 Highways, namely 95.03%>90%.